Peningkatan Hasil Belajar PAI Menggunakan Model Make A Macth di Kelas V SDN 03 Koto Pulai - Ikhsar, Jamiatul (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education in fifth-grade students at SDN 03 Koto Pulai through the implementation of the Make a Match learning model. The research was conducted in two cycles using the Classroom Action Research (CAR) method. The results showed that in Cycle I, there was an improvement in student learning outcomes, although not optimal. Only 57.14% of students achieved mastery. However, student activity in the learning process and critical thinking skills still need improvement. In Cycle II, plans for improvement, including enhancing communication between the teacher and students and increasing student participation, are expected to further improve learning outcomes. This study suggests that the Make a Match model be continually applied and adapted to the students’ needs.